2011
DOI: 10.1016/j.pain.2011.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Affective brain regions are activated during the processing of pain-related words in migraine patients

Abstract: Several brain areas that constitute the neural matrix of pain can be activated by noxious stimuli and by pain-relevant cues, such as pictures, facial expressions, and pain-related words. Although chronic pain patients are frequently exposed to pain-related words, it remains unclear whether their pain matrix is specifically activated during the processing of such stimuli in comparison to healthy subjects. To answer this question, we compared the neural activations induced by verbal pain descriptors in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 68 publications
12
67
0
Order By: Relevance
“…Altered activity, functional connectivity, and grey matter density of this brain structure have also been reported in migraineurs [60,69]. Indeed, migraineurs were identified to have structural and functional cerebral abnormalities in the prefrontal cortex, the rostral ACC, the somatosensory cortex, the orbitofrontal cortex, and insular cortex [70,71]. Migraineurs were found to have reduced cortical thickness in both the ACC and the insular cortex, another brain structure involved in processing the emotional component of pain.…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 94%
See 1 more Smart Citation
“…Altered activity, functional connectivity, and grey matter density of this brain structure have also been reported in migraineurs [60,69]. Indeed, migraineurs were identified to have structural and functional cerebral abnormalities in the prefrontal cortex, the rostral ACC, the somatosensory cortex, the orbitofrontal cortex, and insular cortex [70,71]. Migraineurs were found to have reduced cortical thickness in both the ACC and the insular cortex, another brain structure involved in processing the emotional component of pain.…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 94%
“…Responsive salience networks in the brain are disrupted or dysregulated in chronic pain patients, whereby dysregulated brain salience systems may be overly responsive to certain types of stimuli because they cannot properly filter/process information [79]. This hypothesis is evident in migraineurs where functional imaging studies identified that migraine patients viewing pain-related words exhibited enhanced activation in the insular cortex and orbitofrontal cortex, compared to healthy control subjects [71]. The orbitofrontal cortex is involved in judging the affective value of reinforcing stimuli and driving the individual towards goal-directed behavior, and makes substantial connections with the amygdala, striatum, and the ACC [80].…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 99%
“…Research suggests that pain receptor areas of the brain may be activated by trigger words and/or descriptions of pain that then act as verbal primers for perception (Eck, Richter, Straube, Miltner, & Weiss, 2011;Richter, Eck, Straube, Miltner, & Weiss, 2010). During the focus groups the midwives discussed how they presented information about the injection pain to women in their care; references to everyday phenomena and language that emphasized the brevity of the sensation were common:…”
Section: Sub-theme: Pain Talk -Describing the Injection Pain To Womenmentioning
confidence: 99%
“…Abnormalities in the connectivity and activity of these resting-state networks have previously been reported during the interictal phase of migraine. 4,5 Patients were recruited as part of a larger study investigating the migraine-inducing properties of PACAP38 and VIP and their effects on extracranial and intracranial arterial diameter among other factors. …”
mentioning
confidence: 99%
“…Abnormalities in the connectivity and activity of these resting-state networks have previously been reported during the interictal phase of migraine. 4,5 Patients were recruited as part of a larger study investigating the migraine-inducing properties of PACAP38 and VIP and their effects on extracranial and intracranial arterial diameter among other factors. 3 A double-blind randomized design was used to allocate 24 patients to receive an IV infusion of either PACAP38 (10 pmol/kg/min) or VIP (8 pmol/kg/min) over 20 minutes on the first study day.…”
mentioning
confidence: 99%